A STUDY ON BUSINESS GROWTH FACTOR TO CREATE INNOVATION PROCESS OF COMPANIES (CASE STUDY IN REFRIGERATED TRUCK COMPANY) - Fujiyama, Kojiro; Oktavianty, Oke; Yano, Shoichi; Haruyama, Shigeyuki (JEMIS (Journal of Engineering & Management in Industrial System), 2022)
Previous studies into the elements that influence the growth factors of SME show that creating new values by innovation is a key to sustainable business progress, and also that there are constant demands for creating innovation in the society. In response to such demands, there have been various models developed on creating innovation. Many have pointed out the importance of grasping the innovation not as a solution for a single problem but for the whole process of engineering development - as a system which integrates the product manufacturing, engineering and business application. Furthermore, such innovation is increasingly considered significant in the studies on the elements influencing the factors that lead to constant progress of business of, not only SME, but also companies in general. In this study, we took an example of a Japanese manufacturer which achieved the position of a niche top and has been successful in continually growing in business to investigate on and analyze the following two subjects; â€œthe elements influencing the growth factor of an enterpriseâ€ and â€œthe transition of the growth factors in accordance with each product lifecycleâ€. The result hereby shows the different elements that can create a value affecting the business growth factors in the respective stages of product lifecycle, such as Introduction, Growth and Maturity.Â